Beta Radiation Enhanced Thermionic Emission from Diamond Thin Films - Croot, Alex; Wan, Gary; Rowan, Alex; Andrade, Hugo D.; Smith, James A.; Fox, Neil A. (Frontiers in Mechanical Engineering, 2017)
Diamond-based thermionic emission devices could provide a means to produce clean and renewable energy through direct heat-to-electrical energy conversion. Hindering progress of the technology are the thermionic output current and threshold temperature of the emitter cathode. In this report, we study the effects on thermionic emission caused by in-situ exposure of the diamond cathode to beta radiation. Nitrogen-doped diamond thin films were grown by microwave plasma chemical vapour deposition on molybdenum substrates. The hydrogen-terminated nano-crystalline diamond was studied using a vacuum diode setup with a 63Ni beta radiation source-embedded anode, which produced a 2.7-fold increase in emission current compared to a 59Ni-embedded control. The emission threshold temperature was also examined to further assess the enhancement of thermionic emission, with 63Ni lowering the threshold temperature by an average of 58 ± 11 oC compared to the 59Ni control. Various mechanisms for the enhancement are discussed, with a satisfactory explanation remaining elusive. Nevertheless, one possibility is discussed involving excitation of pre-existing conduction band electrons that may skew their energy distribution toward higher energies.